Eumycetoma due to Parathyridaria percutânea in an immunosuppressed patient - an imported case in Portugal - Fraga, Marta (2022)
Abstract publicado em: J Fungi (Basel). 2021 Nov; 7(11):916. pp. 223-24. (P262). doi: 10.3390/jof7110916